Respiratory Regulation - The Molecular Approach - Pokorski, Mieczysław (Advances in experimental medicine and biology, 2013)
This book, an international collaborative effort in the area of molecular respiratory research, showcases a broad range of multidisciplinary approaches to unravel and analyze the underlying mechanisms of a spectrum of respiratory ailments. It discusses immunological and genetic respiratory disorders, cancer, respiratory allergies and cough, sleep disordered breathing and many others. Exciting new results and up-to-date critical overviews of widely debated topics pertaining to respiratory disorders are presented. The contributions provide evidence for the growing interest of the international community of researchers in the field of respiration. The book incorporates modern molecular approaches to diagnostic and treatment solutions, underscoring the need for rational, evidence-based treatment methods. Combining cutting edge basic and clinical research with expert knowledge and experience this book is essential reading for medical students, research scientists and practicing specialists in pulmonology, immunology and allergology.
Description based upon print version of record